2015
DOI: 10.1039/c5cp02498f
|View full text |Cite
|
Sign up to set email alerts
|

Drawing dependent structures, mechanical properties and cyclization behaviors of polyacrylonitrile and polyacrylonitrile/carbon nanotube composite fibers prepared by plasticized spinning

Abstract: Drawing to change the structural properties and cyclization behaviors of the polyacrylonitrile (PAN) chains in crystalline and amorphous regions is carried out on PAN and PAN/carbon nanotube (CNT) composite fibers. Various characterization methods including Fourier transform infrared spectroscopy, differential scanning calorimetry, X-ray diffraction and thermal gravimetric analysis are used to monitor the structural evolution and cyclization behaviors of the fibers. With an increase of the draw ratio during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 46 publications
(71 reference statements)
0
14
0
Order By: Relevance
“…For the FTIR spectra of the PAN bers, the peaks in the range of 2180-2260 cm À1 can be ascribed to three types of C^N groups: un-reacted nitrile at 2242 cm À1 , conjugated nitrile at 2210 cm À1 and b-amino nitrile at 2190 cm À1 . 28,29 As shown in Table 3 and Fig. 2, B 3 shows a higher F c than D 3.…”
Section: Ftir Analysismentioning
confidence: 69%
“…For the FTIR spectra of the PAN bers, the peaks in the range of 2180-2260 cm À1 can be ascribed to three types of C^N groups: un-reacted nitrile at 2242 cm À1 , conjugated nitrile at 2210 cm À1 and b-amino nitrile at 2190 cm À1 . 28,29 As shown in Table 3 and Fig. 2, B 3 shows a higher F c than D 3.…”
Section: Ftir Analysismentioning
confidence: 69%
“…In addition to organic materials, inorganic materials such as carbon nanotubes (CNTs) and functionalized CNTs have been mixed with the PAN precursor. [7,21,22] CNTs enhance the mechanical properties of the carbon fiber. Since PAN is already a one-dimensional crystallized material consisting of carbon atoms, it can easily stack upon the CNTs to form a graphitic structure.…”
Section: Introductionmentioning
confidence: 99%
“…Among various types of polymer-CNT nanocomposite fiber, polyacrylonitrile (PAN) has been among the most studied polymeric system 10 12 . Li et al 3 studied the effect of drawing on the mechanical properties of the PAN/multi-wall carbon nanotube (MWNT) composite fiber. Chae et al investigated enhancing PAN-CNT composites by gel-spinning 4 , 5 and CNT-exfoliation 6 processes, and Wang et al 7 showed that the mechanical properties of PAN-CNT nanocomposites were enhanced by the orientation of nanocomposite CNTs during deformation.…”
Section: Introductionmentioning
confidence: 99%
“…PAN polymer is a well-known precursor for carbon fiber, and recent studies have shown that even nanometer-scale defects can be of critical failure site 21 . A number of studies [2][3][4][5][6][7] on PAN/CNT composite fibers have been conducted for the last two decades to improve carbon fiber properties further. Therefore, it is essential to understand the role of CNT for the defect structure development in the precursor fiber processing stage.…”
mentioning
confidence: 99%